Flexural vibration of a jump ski in flight - Shionoya, A.; Kobayashi, T.; Saijo, T.; Ogata, K.; Matsuhashi, T. (Bio-mechanisms of swimming and flying. Fluid dynamics, biomimetic robots, and sports science, 2008)
The purposes of this study were to develop a system for measuring the flexural vibration of a jump ski in flight and to measure the vibration of a ski in flight using this system. To measure the flexural vibration of a jump ski in flight, accelerometers were installed on a ski plate. By means of accelerometers, vibrations of a ski were detected in flight and were recorded to a data recorder. After flight this data was transferred to a computer, after which it was transformed into a power spectrum by means of FFT. In actual flight, an amplifier and a data recorder were inserted into a backpack attached to a jumper`s jump suit. The vibrations were analyzed in the following phases; approach, take off, flight and landing. From approach to landing, few natural vibration frequencies between 10 and 200[Hz], as estimated by the impulse response, were detected. A low frequency of about 10 [Hz] was detected in nearly every phases. Furthermore, at landing, a low frequency components band between 40 and 70 [Hz] was detected at the top of the ski, because the jumper landed on the tail of the ski. In addition an acceleration amplitude of over 9800[m/sec2] was detected at the top of a ski in landing.